2020
DOI: 10.1212/wnl.0000000000009263
|View full text |Cite
|
Sign up to set email alerts
|

Journal Club: High-dose methylprednisolone for acute traumatic spinal cord injury

Abstract: Methylprednisolone is a corticosteroid medication used in acute traumatic spinal cord injury (SCI) to tackle secondary injury cascades. Its use in acute SCI has been the subject of controversy for over 30 years. The second National Acute Spinal Cord Injury Study (NASCIS-2) demonstrated a small benefit of methylprednisolone, 1 though this conclusion was derived from a post hoc subgroup analysis. 2 Studies that followed did not reach the same conclusion and reported potential adverse effects of the drug. 3 Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Thus, it is critical to develop effective drugs. Currently, melatonin (Zhang et al, 2018 ), riluzole (Fehlings et al, 2021a ), Rho inhibitors (Fehlings et al, 2021b ), and methylprednisolone (Liu et al, 2020 ) have been evaluated in clinical and preclinical trials. The efficacy of these drugs remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is critical to develop effective drugs. Currently, melatonin (Zhang et al, 2018 ), riluzole (Fehlings et al, 2021a ), Rho inhibitors (Fehlings et al, 2021b ), and methylprednisolone (Liu et al, 2020 ) have been evaluated in clinical and preclinical trials. The efficacy of these drugs remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…§"Others" included "Injuries caused by others," "Work-related injuries," "sharp injuries," "Massage-related injuries," "Electric shock injuries," "Gunshot wounds," "Crush injuries," and "Iatrogenic injury. [59][60][61] In this study, the utilization rate of high-dose ( ≥ 500 mg) MPSS/MP was only 4.6% within eight hours, and there was no significant sex difference at the time of initiation.…”
Section: Discussionmentioning
confidence: 53%
“…However, AOSpine recommended a high dose of MPSS/MP within eight hours of ASCI as a treatment option in 2017 57 . Some surveys found that, despite the great controversy, most patients preferred MPSS/MP early in injury 59–61 . In this study, the utilization rate of high-dose (≥500 mg) MPSS/MP was only 4.6% within eight hours, and there was no significant sex difference at the time of initiation.…”
Section: Discussionmentioning
confidence: 61%
“…1,25,38,66 The corticosteroid methylprednisolone has also been applied to reduce secondary immunological injury after SCI, but its use is limited by controversy over the balance between its efficacy and potential consequences relating to induction of a broadly immunosuppressive state. 12–14,51,62,81 By contrast, PLG NPs have selectively reprogrammed monocytes and neutrophils, reducing excessive early immune responses that initiate further neurological damage. 67 Importantly, with treatment cessation after 7 days after injury, proregenerative cytokine-mediated signaling is allowed to proceed without interruption.…”
Section: Discussionmentioning
confidence: 99%
“…Methylprednisolone has been used to reduce neuropathic pain post-SCI, yet it remains controversial because of treatment-associated adverse effects. [12][13][14]51,62,81 Nanoparticles (NPs) can be used as drug delivery platforms to distribute anti-inflammatory factors that modulate peripheral neuropathic pain responses through selective immune reprogramming. 5,11,63 Alternatively, poly(lactide-co-glycolide) (PLG) NPs, which do not have any active pharmaceutical ingredient, target scavenger receptors on circulating monocytes and neutrophils because of their size and surface charge and reprogram peripheral immune cells through drug-independent mechanisms, ultimately reducing monocyte and neutrophil accumulation at the injury.…”
Section: Introductionmentioning
confidence: 99%